Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Promosi Social Media Terhadap Keputusan Pembelian Konsumen Di CV Semanis Situbondo (Pada Pembelian Minuman Booba Di CV Semanis Situbondo) - Qamar, Sariful; Arifin, Rois; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Product quality is the superiority of a product which explains the ability of a product to meet predetermined product quality requirements or specifications. CV Semanis Situbondo operates in the iced tea beverage sector with various flavors and there is also the booba drink which is also well known to the public. This business, which was founded in 2019, is one of several drink sellers that have started to mushroom recently and keep up with the times. From this background the questions arise, 1. How do service product quality and media promotion simultaneously influence consumer decisions? How does product quality influence purchasing decisions?The method used in this research is qualitative, the data comes from primary data which obtains direct responses from research subjects, namely customers who have purchased the available boba drinks. This research shows that firstly, the better the product quality, the higher the consumer's purchasing decision in purchasing a product. Second, the better the quality of service provided by producers to consumers, the more it will influence consumer purchasing decisions in purchasing drinks from CV products. As sweet as Situbondo has experienced an increase. Third, the better and more interesting the social media promotion that is carried out will get the public's attention so that beautiful product consumers will be interested and consumers will buy drinks. Keywords: Product Quality, Social Media Promotion Service Quality And Consumer Purchase Decisions